PENGEMBANGAN MEDIA VISUAL SCRAPBOOK PADA TEMA PERISTIWA DALAM KEHIDUPAN DI KELAS V SDN SUKASABA 1 PANDEGLANG - Dewi Lestari Dewi; Rina Yuliana; M. Taufik (STKIP Subang, 2022)
The development of this learning media is a process of activities carried out to produce a learning media based on existing theories and product validation that researchers have made so that they are suitable for use in learning activities. This study aims to determine: the results of the design of visual scrapbook media development on the theme of 7 events in life. The purpose of this thesis is for researchers to determine learning outcomes using learning media using Scrapbook Media. Methods This research uses the Risech and delepoment (R&D) research method. The subjects in this study were the fifth grade students of SDN Sukasaba 1 Pandeglang Regency for the academic year 2021/2022, totaling 16 students, with 10 female students and 10 male students. The data collection instrument in this study used observation sheets and interviews. From the results of the Scrapbook visual media research on the material of events in life, there is an increase in learning in the classroom. And the results of the validation of media experts obtained 85% categorized as very feasible, the results of material expert validation obtained 85% categorized as very feasible, the results of linguistic expert validation 84% were categorized as very feasible and the results of the student responses obtained 81.5% categorized as very good. From the results of these studies, it is shown that learning on the material of events in life using visual media Scrapbook is able to increase the readiness and focus of students in understanding learning faster. Therefore, in learning events in life, it is recommended for teachers to use the Scrapbook media because it can improve learning outcomes and make students understand learning faster.